Added Value of Crystal Coconut Sugar in Women Farmers Group Tetes Mancung Cilongok District Banyumas Regency - Ratna Satriani; Taufik Budhi Pramono (Indonesian Journal of Food Technology, 2022)
KWT Tetes Mancung is one of the women's groups that produce crystal coconut sugar. An effort to obtain maximum profit is largely determined by the management and combination of factors of production that are used appropriately. Increasing the added value of a product can provide benefits for business actors. The process of producing coconut sap into crystal coconut sugar is able to increase the selling price of crystal coconut sugar so that the group's income also increases. This study aims to: (1) determine the characteristics of the craftsmen, and (2) determine the added value of crystalline coconut sugar. Data collection was carried out on March 1 to March 31, 2021. The research method used was the case study method. The analytical tools used are descriptive analysis and added value analysis. The results showed that: 1) the characteristics of crystal coconut sugar craftsmen in KWT from the level of education as much as 42 % had basic education (SD), the number of dependents of the family was 2-4 people, the average craftsman experience was 7-10 years and the average coconut tree which tapped 22 trees. 2) the added value of coconut sap which is processed into crystal coconut sugar is Rp 5,159,00 or 35.97 percent.